(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2024)
Objective: To analyze, from the maternal perspective, the importance of the guidance provided by stomal therapy nurses for the care of children with intestinal stomas. Method: This qualitative, descriptive-exploratory study collected data through semistructured interviews conducted from June to November 2019. The data were subjected to thematic content analysis as suggested by Bardin. Results: Nine mothers of children with stomas were interviewed. They emphasized the importance of guidance from stomal therapy nurses, which contributed to their confidence in performing specific stoma care and using specific products correctly. In addition, an improvement in peristomal dermatitis was noted. Mothers also expressed satisfaction with the information they received about the surgical procedure. Conclusion: The guidance received by the mothers was crucial due to the lack of information about the disease and the specific care required for their child with a stoma. This guidance fostered a sense of gratitude, especially for the redirection provided by the stomal therapy nurse in addressing care difficulties.